The Use of Satire Language Style in Dakwah Videos and its Implications For the Learning of Indonesian Language at School - Arlinda, Arlinda; Baadilla, Irwan (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to the use of satirical language style in dakwah videos and its implications for the learning of the Indonesian language at school. The research method used is descriptive qualitative with data analysis techniques. The data collection technique used in this study is the note-taking technique, namely observation, note-taking, and documentation. The research data was obtained from videos, preaching, and dialogue on the YouTube channel